2018
DOI: 10.1002/slct.201802282
|View full text |Cite
|
Sign up to set email alerts
|

SingaCycleTM‐A1‐Catalyzed Successive Suzuki‐Miyaura and Buchwald Couplings for the Synthesis of Various New Pyridine Analogues

Abstract: A new diversified, rapid and easily accessible, N‐heterocyclic carbene based palladacycle, SingaCycleTM‐A1 exploited for the cross coupling reactions on heterocyclic amines. This Pd‐NHC catalyst is considered to be merely stable and takes part in dynamic conversion of various organic functionalities. Herein, we report its first time use in the synthesis of C‐ and N‐ diaryl/ heteroaryl pyridine analogues from the less active parent 5‐bromopyridine‐2‐amine via sequential Suzuki‐Miyaura and Buchwald couplings. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…TON=Ratio of moles of reactant to ratio of moles of catalyst used multiplies with percentage of yield. TOF=Turnover number per hour [18b,c] …”
Section: Resultsmentioning
confidence: 99%
“…TON=Ratio of moles of reactant to ratio of moles of catalyst used multiplies with percentage of yield. TOF=Turnover number per hour [18b,c] …”
Section: Resultsmentioning
confidence: 99%
“…The present method has been found to be highly efficient for the heteroaryl bromides including 2‐bromothiophene, 2‐bromopyridine, and 2‐amino‐5‐bromopyridine to provide excellent yields of coupling products in short reaction times (20–30 min) (Table 2, products 3ac – 3ae ). Moreover, high degree of chemoselectivity was observed in the reaction of 4‐bromoaniline and phenylboronic acid or 2‐amino‐5‐bromopyridine and 2,4‐fluorophenylboronic acid, [ 61 ] that is, the selective reactivity of halogen attached position over free –NH 2 (Table 2, products 3q and 3ae ), which may usually results the Chan‐Lam coupling. Furthermore, the sensitive functional groups, formyl, keto, carboxyl, ester, nitro, cyano, amino, and chloro, present on both the aryl halides and ABAs were unaffected in these reactions.…”
Section: Resultsmentioning
confidence: 99%
“…This kind of construction has evolved some triazolo-, imidazolo-and pyrimidino-fused acridones so far, this piperazine fused acridone frame linking alkyl/ aryl moieties with amide linker is a novel accomplishment to the existing array of acridones. As Pd(OAc) 2 -Xantphos is used as a potential catalyst-ligand system for C-N coupling 44 , here we have extended the use of Cs 2 CO 3 -Pd(OAc) 2 -Xantphos system in producing the acridone ring by forming a C-N linkage through N-arylation process. The chemical structures of the synthesized compounds (7a-s) of the study were confirmed by IR, 1 H, 13 C and mass spectrometry analyses and all the spectral responses were observed in their expected standard range, and cor- 7r, 7l, 7o, 7a, 7d, 7b, 7e, 7i and 7q having the substitutions like p-hydroxybenzoyl, p-fluorobenzoyl, benzoyl, p-(trifluoromethyl)benzoyl, picolinoyl, cyclopropyl-acetyl, 3-nicotinoyl, 6-methylpicolinoyl, trifluoromethylpicolinyl and 3-fluorobenzoyl groups on acridone fused piperazine moiety.…”
Section: Resultsmentioning
confidence: 99%